Halal Supply Chain Performance: The Impact of Supply Chain Integration Strategy in Indonesian SMEs - Umari Abdurrahim Abi Anwar; Agus Rahayu; Lili Adi Wibowo; Mokhamad Adib Sultan (UPT Publikasi Ilmiah UNISBA, 2026)
This study investigates the impact of Supply Chain Integration (SCI) on Halal Supply Chain Performance (HSCP) among halal-certified SMEs in Indonesia. Using a purposive sampling approach, data were collected from 60 medium-sized enterprises through structured questionnaires and follow-up interviews, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study focuses on three dimensions of SCI: internal, external, and information integration. The results indicate that SCI has a significant and substantial effect on HSCP (R² = 0.750, p < 0.001), with information integration emerging as the most critical driver, particularly in enhancing traceability and transparency. Internal integration is strongly associated with process efficiency and quality assurance, while external integration strengthens compliance and customer satisfaction. These findings suggest that halal-certified SMEs can overcome resource limitations and improve competitiveness by prioritizing digital information systems, structured internal procedures, and strategic external collaboration. The study contributes to SCI and halal supply chain literature by highlighting the distinctive dynamics of halal-certified SMEs and provides actionable guidance for policymakers and industry leaders in designing digital infrastructure support, capacity-building programs, and affordable traceability tools.